2022
DOI: 10.1002/smll.202201402
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Ultrahigh Effective Surface Charge Density of Direct‐Current Triboelectric Nanogenerator in High Humidity

Abstract: As an emerging energy‐harvesting technology, the triboelectric nanogenerator (TENG) is considered a powerful driving force toward the new‐era of Internet of Things and artificial intelligence, but its output performance is dramatically influenced by environmental humidity. Herein, a direct current TENG (DC‐TENG) based on the triboelectrification effect and electrostatic breakdown is reported to address the problem of output attenuation in high humidity environments for the conventional TENGs. It is found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…[34][35][36] The direct-current TENG using the principle of electrostatic breakdown can also maintain a good output in the high-humidity environment. 37,38 Although the above methods can effectively alleviate the problem of charge dissipation in high-humidity environments, it is still difficult to break through the limit of transferred charge density due to the inherent limitation of surface electrostatic charges for insulator materials. On the other hand, the tribovoltaic effect which transitions the study of the TENG from insulators to semiconductor materials could utilize the interface friction on the semiconductor interface to generate direct current.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] The direct-current TENG using the principle of electrostatic breakdown can also maintain a good output in the high-humidity environment. 37,38 Although the above methods can effectively alleviate the problem of charge dissipation in high-humidity environments, it is still difficult to break through the limit of transferred charge density due to the inherent limitation of surface electrostatic charges for insulator materials. On the other hand, the tribovoltaic effect which transitions the study of the TENG from insulators to semiconductor materials could utilize the interface friction on the semiconductor interface to generate direct current.…”
Section: Introductionmentioning
confidence: 99%
“…The technique utilizes an excitation circuit to realize the directional accumulation of charge and provides a more effective method for modifying dielectric materials. Environment factor is also considered in achieving effective surface charge density of DC-TENG as mentioned by (Liu et al, 2022). It is found that high humidity not only enhances the sliding triboelectrification effect of triboelectric materials but also improves the DC-TENG output.…”
Section: Introductionmentioning
confidence: 99%
“…In friction layers with a porous structure, the presence of interior pores provides an additional surface area, which significantly enhances the surface charge density. This accumulation of charge on the porous surface has the potential to improve the output performance of a TENG. We measured the specific surface area of SF@MXene-A at different MXene concentrations by using the Brunauer–Emmett–Teller (BET) specific surface area detection method. Figure d shows the specific surface area of pristine SF and the SF@MXene composite with MXene concentrations of 40%, 50%, and 60%.…”
mentioning
confidence: 99%